Come costruirsi un grigliato NTv2 in casa - Sferlazza, Ernesto (GEOmedia, 2014)
For those working with spatial data in a geographic information system (GIS), one of the most frequent activities (and, not infrequently, even frustrating) concerns the transformation of coordinates between different reference systems. Among the various methods used to make coordinate transformations between different datum, those who make use of gratings deviations allow for a high degree of accuracy overwide geographic areas, provided, however, that they are reliable values of the deviations assigned to the nodes. In the article, after having explained the standard specifications NTv2, is described, in broad terms, the general procedure that allows us to estimate variances when the coordinates are known, referring to two different datum, a set of points evenly distributed on area of interest.